Effective Gene Delivery into Human Stem Cells with a Cell‐Targeting Peptide‐Modified Bioreducible Polymer. Issue 17 (16th December 2014) - Beloor, Jagadish; Ramakrishna, Suresh; Nam, Kihoon; Seon Choi, Chang; Kim, Jongkil; Kim, Sung Hwa; Cho, Hyong Jin; Shin, HeungSoo; Kim, Hyongbum; Kim, Sung Wan; Lee, Sang‐Kyung; Kumar, Priti
<x xml:space="preserve">Abstract</x> Stem cells are poorly permissive to non‐viral gene transfection reagents. In this study, we explored the possibility of improving gene delivery into human embryonic (hESC) and mesenchymal (hMSC) stem cells by synergizing the activity of a cell‐binding ligand with a polymer that releases nucleic acids in a cytoplasm‐responsive manner. A 29 amino acid long peptide, RVG, targeting the nicotinic acetylcholine receptor (nAchR) was identified to bind both hMSC and H9‐derived hESC. Conjugating RVG to a redox‐sensitive biodegradable dendrimer‐type arginine‐grafted polymer (PAM‐ABP) enabled nanoparticle formation with plasmid DNA without altering the environment‐sensitive DNA release property and favorable toxicity profile of the parent polymer. Importantly, RVG‐PAM‐ABP quantitatively enhanced transfection into both hMSC and hESC compared to commercial transfection reagents like Lipofectamine 2000 and Fugene. ∼60% and 50% of hMSC and hESC were respectively transfected, and at increased levels on a per cell basis, without affecting pluripotency marker expression. RVG‐PAM‐ABP is thus a novel bioreducible, biocompatible, non‐toxic, synthetic gene delivery system for nAchR‐expressing stem cells. Our data also demonstrates that a cell‐binding ligand like RVG can cooperate with a gene delivery system like PAM‐ABP to enable transfection of poorly‐permissive cells.